Pemanfaatan Sarana Dan Prasarana Sebagai Pendukung Keaktifan Siswa Dalam Pembelajaran Di Sekolah Dasar - Nurul Islamiah; Aryanti Fazriah; Welki Bahri Sigiro (Pusat Riset dan Inovasi Nasional, 2024)
In the world of education, especially in the learning process, the use of facilities and infrastructure has an important role in creating conducive learning and attracting student interest. This research aims to determine and describe the use of facilities and infrastructure to support student activity in learning in elementary schools. The type of research used is qualitative research to explore situations and conditions in the field. The main instrument of this research refers to field notes. Data collection was carried out using several techniques, namely; (a) observation, (b) interview. All data is collected and studied descriptively to obtain reliable and reliable findings. The results of the research show that the use of facilities and infrastructure at SDN Cipare is carried out well with the availability of adequate facilities and infrastructure and supports the learning process which provides great benefits for students' active learning and enthusiasm in learning.